Plasma mitochondrial DNA levels are associated with acute lung injury and mortality in septic patients - Mao, Jia-yu; Li, Dong-kai; Zhang, Hong-min; Wang, Xiao-ting; Liu, Da-wei (BMC pulmonary medicine, 2021)
Mitochondrial DNA (mtDNA) is a critical activator of inflammation. Circulating mtDNA released causes lung injury in experimental models. We hypothesized that elevated plasma mtDNA levels are associated with acute lung injury (ALI) in septic patients. We enrolled 66 patients with sepsis admitted to the Department of Critical Care Medicine of Peking Union Medical College Hospital between January 2019 and October 2019. Respiratory, hemodynamic and bedside echocardiographic parameters were recorded. Plasma mtDNA, procalcitonin, interleukin 6, and interleukin 8 levels were examined. Plasma mtDNA levels within 24 h after admission were significantly increased in the group of septic patients with ALI [5.01 (3.38-6.64) vs 4.13 (3.20-5.07) log copies/µL, p 0.0172]. mtDNA levels were independently associated with mortality (hazard ratio, 3.2052; 95% CI 1.1608-8.8500; p 0.0253) and ALI risk (odds ratio 2.7506; 95% CI 1.1647-6.4959; p 0.0210). Patients with high mtDNA levels had worse outcomes, and post hoc tests showed significant differences in 28-day survival rates. Increased mtDNA levels were seen in patients with abdominal infection. Increased plasma mtDNA levels within 24 h after admission were significantly associated with ALI incidence and mortality in septic patients.